2022
DOI: 10.1177/09697764221129532
|View full text |Cite
|
Sign up to set email alerts
|

Empowering policies for grassroots welfare initiatives: Blending social innovation and commons theory

Abstract: Social innovation scholars see grassroots welfare initiatives as being potentially empowering. However, they also argue that this potential is enhanced when these initiatives receive support from local governments through a bottom-linked approach to social innovation. This article examines how empowering policies for grassroots welfare initiatives can be provided within a bottom-linked approach, while considering the reservations expressed by critical urban scholars on the link between them. By introducing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…However, other work on mutual aid and common infrastructures has suggested that they are rarely free of institutional entanglements, from their very inception. Writing about the forms of care and politics that were forged in Barcelona in response to post-Global Financial Crisis austerity, Bianchi (2022aBianchi ( , 2022b argues that mutual aid and other urban commons initiatives are often sustained by forms of state support that are frequently unrecognised. Similarly, Gibson-Grahamet al (2016, p. 207) see commoning initiatives such as mutual aid taking the form of assemblages that "may include social movements and grass-roots organisations but also governments, institutions and firms; they may include non-market mechanisms but also markets ….…”
Section: Mutual Aid As Care Infrastructurementioning
confidence: 99%
“…However, other work on mutual aid and common infrastructures has suggested that they are rarely free of institutional entanglements, from their very inception. Writing about the forms of care and politics that were forged in Barcelona in response to post-Global Financial Crisis austerity, Bianchi (2022aBianchi ( , 2022b argues that mutual aid and other urban commons initiatives are often sustained by forms of state support that are frequently unrecognised. Similarly, Gibson-Grahamet al (2016, p. 207) see commoning initiatives such as mutual aid taking the form of assemblages that "may include social movements and grass-roots organisations but also governments, institutions and firms; they may include non-market mechanisms but also markets ….…”
Section: Mutual Aid As Care Infrastructurementioning
confidence: 99%